2010
DOI: 10.1021/jf101513r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Isoflavone Aglycones and Equol in Soy Milks Fermented by Food-Related Lactic Acid Bacteria and Their Effect on Human Intestinal Caco-2 Cells

Abstract: One hundred and three strains of lactic acid bacteria, isolated from various food ecosystems, were assayed for β-glucosidase activity toward p-nitrophenyl-β-D-glucopyranoside substrate. Lactobacillus plantarum DPPMA24W and DPPMASL33, Lactobacillus fermentum DPPMA114, and Lactobacillus rhamnosus DPPMAAZ1 showed the highest activities and were selected as the mixed starter to ferment various soy milk preparations, which mainly differed for chemical composition, protein dispersibility index, and size dimension. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 32 publications
7
57
0
Order By: Relevance
“…This strain showed the highest β-glucosidase activity among the strains studied. Di Cagno et al (15) found similar results in a study in which soymilk with food-related lactic acid bacteria contained 0.9 mg/100 mL of equol after 96 h of fermentation. The authors proposed correlations between the growth characteristics of the bifidobacteria in soymilk, their β-glucosidase activity, and the conversion of isoflavone glycosides into aglycone forms.…”
Section: )supporting
confidence: 67%
See 2 more Smart Citations
“…This strain showed the highest β-glucosidase activity among the strains studied. Di Cagno et al (15) found similar results in a study in which soymilk with food-related lactic acid bacteria contained 0.9 mg/100 mL of equol after 96 h of fermentation. The authors proposed correlations between the growth characteristics of the bifidobacteria in soymilk, their β-glucosidase activity, and the conversion of isoflavone glycosides into aglycone forms.…”
Section: )supporting
confidence: 67%
“…A number of bacteria in intestinal flora have also been reported to be responsible for this conversion (14). However, the formation of equol during soymilk fermentation without the presence of bacteria from intestinal microflora, has also been considered in some studies that correlate the equol formation with the use of enzymes (15,34,35).…”
Section: )mentioning
confidence: 97%
See 1 more Smart Citation
“…Inhibition of the NF-κB pathway was able to reduce the ROS induced cellular oxidative damage, and reduced the human IBD [34]. In addition, soybean milk fermented by mixed LAB starter that including Lactobacillus plantarum, Lactobacillus fermentum, and Lactobacillus rhamnosus were also markedly inhibited the chemokine IL-8 production in IL-1β treated Caco-2 cells [35].…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, a number of the nutrients, e.g. isoflavones from soy, cannot be absorbed without the aid of microbes in the intestine (Di Cagno et al 2010, Ding and Shah 2010, Rekha and Vijayalakshmi 2010. Nonetheless, a healthy diet can reduce the chances of developing cancer.…”
Section: Dietmentioning
confidence: 99%